Molecular cloning and expression of the cDNA for the hamster alpha 1-adrenergic receptor. - Cotecchia, S (1988)
The cDNA for the Syrian hamster alpha 1-adrenergic receptor has been cloned with oligonucleotides corresponding to the partial amino acid sequence of the receptor protein purified from DDT1MF-2 smooth muscle cells. The deduced amino acid sequence encodes a 515-residue polypeptide that shows the most sequence identity with the other adrenergic receptors and the putative protein product of the related clone G-21. Similarities with the muscarinic cholinergic receptors are also evident. Expression studies in COS-7 cells confirm that we have cloned the alpha 1-adrenergic receptor that couples to inositol phospholipid metabolism.